2013
DOI: 10.1371/journal.pone.0074374
|View full text |Cite
|
Sign up to set email alerts
|

Did Terrestrial Diversification of Amoebas (Amoebozoa) Occur in Synchrony with Land Plants?

Abstract: Evolution of lineage diversification through time is an active area of research where much progress has been made in the last decade. Contrary to the situation in animals and plants little is known about how diversification rates have evolved in most major groups of protist. This is mainly due to uncertainty about phylogenetic relationships, scarcity of the protist fossil record and the unknown diversity within these lineages. We have analyzed the evolutionary history of the supergroup Amoebozoa over the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 56 publications
3
27
0
Order By: Relevance
“…This is also in agreement with previous studies that found a large undetected diversity within this lineage, and highlights the importance of unraveling it to understand its evolution (Romeralo et al, 2011;Fiz-Palacios et al, 2013;Tekle et al, 2016;Kang et al, 2017).…”
Section: Eukaryotic Diversity In Paraná River Is Similar To Other Fresupporting
confidence: 92%
“…This is also in agreement with previous studies that found a large undetected diversity within this lineage, and highlights the importance of unraveling it to understand its evolution (Romeralo et al, 2011;Fiz-Palacios et al, 2013;Tekle et al, 2016;Kang et al, 2017).…”
Section: Eukaryotic Diversity In Paraná River Is Similar To Other Fresupporting
confidence: 92%
“…Of course, without fossil calibration points, the error bars in these molecular clocks are necessarily large. That said, the clock estimates of Fiz-Palacios et al [39] and Lahr et al [40] are consistent with the hypothesis that terrestrial arcellinids, diversified as land plants, began to transform terrestrial ecosystems. The position of Leptochlamys within arcellinid phylogeny remains uncertain, as it has not been sequenced and so is absent from modern molecular analyses.…”
Section: And Discussionsupporting
confidence: 60%
“…Spo11 will doubtless be found to have been lost in a number of lineages, perhaps most frequently in newly asexual lineages. In the social amoeba, the genera Dictyostelium, Polysphondylium, and Acytostelium, Spo11 appears to have already been absent in their most recent common ancestor [17] (and unpublished results), which is thought to have lived several hundred million years ago [58]. This is noteworthy because these organisms are believed to be sexual [59].…”
Section: Meiosis In the Absence Of Spo11mentioning
confidence: 83%